Depressive Symptom Clusters in Relation to Body Weight Status: Results From Two Large European Multicenter Studies - Baldofski, Sabrina; Mauche, Nicole; Dogan-Sander, Ezgi; Bot, Mariska; Brouwer, Ingeborg A.; Paans, Nadine P. G.; Cabout, Mieke; Gili, Margarita; van Grootheest, Gerard; Hegerl, Ulrich; Owens, Matthew; Roca, Miquel; et al. (Frontiers in Psychiatry, 2019)
Background: There is strong evidence for a bi-directional association between depression and obesity. Several biological, psychological and behavior-related factors may influence this complex association. Clinical impression and preliminary evidence suggest that patients with a diagnosis of major depressive disorder may endorse very different depressive symptom patterns depending on their body weight status. To date, little is known about potential differences in depressive symptoms in relation to body weight status. Objective: The aim of this analysis is the investigation of potential differences in depressive symptom clusters (mood symptoms, somatic/vegetative symptoms, and cognitive symptoms) in relation to body weight status. Methods: Cross-sectional baseline data were derived from two large European multi-center studies: the MooDFOOD trial and the NESDA cohort study, including persons with overweight and obesity and normal-weight reporting subthreshold depressive symptoms (assessed with the Inventory of Depressive Symptomatology Self Report, IDS-SR30). Different measures for body weight status (waist-to-hip ratio [WHR] and body mass index [BMI]) were examined. Propensity score matching was performed and multiple linear regression analyses were conducted. Results: A total of n = 504 individuals (73.0% women) were analyzed. Results show that more somatic/vegetative depressive symptoms, such as pain, change in appetite and weight, gastro-intestinal symptoms, and arousal-related symptoms, were significantly associated with both a higher BMI and higher WHR, respectively. In addition, being male and older age were significantly associated with higher WHR. Mood and cognitive depressive symptoms did not yield significant associations for both body weight status measures. Conclusions: Somatic/vegetative symptoms and not mood and cognitive symptoms of depression are associated with body weight status. Thus, the results support previous findings of heterogeneous depressive symptoms in relation to body weight status. In addition to BMI, other body weight status measures for obesity should be taken into account in future studies.